2021
DOI: 10.1080/13803395.2021.1937579
|View full text |Cite
|
Sign up to set email alerts
|

How did individual differences in neurocognition and health literacy influence the initial uptake and use of health-related information about COVID-19?

Abstract: Objective: The rapid development of coronavirus disease 2019 (COVID-19) into a pandemic required people to quickly acquire, evaluate, and apply novel complex health-related information about the virus and transmission risks. This study examined the possible interplay between neurocognition and health literacy in the early uptake and use of COVID-19 public health information. Method: Data were collected between April 23 and May 21, 2020, a period during which 42 out of 50 states were under a stay-at-home order.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…These findings correspond with prior studies that show disease related knowledge of medical conditions such as diabetes, hypertension, and heart disease is associated with cognitive functioning (Levinthal et al, 2008;Morrow et al, 2006;Wykes et al, 2017). With respect to COVID-19 knowledge, our findings are consistent with Babicz et al (2021) who found that greater accuracy was predicted by better memory and executive function. As noted by these investigators, an association with memory is intuitive since it is critical for encoding and retention of information.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These findings correspond with prior studies that show disease related knowledge of medical conditions such as diabetes, hypertension, and heart disease is associated with cognitive functioning (Levinthal et al, 2008;Morrow et al, 2006;Wykes et al, 2017). With respect to COVID-19 knowledge, our findings are consistent with Babicz et al (2021) who found that greater accuracy was predicted by better memory and executive function. As noted by these investigators, an association with memory is intuitive since it is critical for encoding and retention of information.…”
Section: Discussionsupporting
confidence: 92%
“…However, the possible impact of cognitive status was not investigated in their study. In contrast, Babicz et al. (2021) found that lower cognitive functioning is associated with poorer knowledge of COVID-19 symptoms.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations